2021
DOI: 10.1038/s41598-021-93873-7
|View full text |Cite
|
Sign up to set email alerts
|

The association between serum selenium concentration and prognosis in patients with heart failure in a Chinese population

Abstract: Whether Selenium (Se) deficiency relates with adverse prognosis in Chinese patients with heart failure (HF) is still unknown. This study aimed to investigate the association of serum Se level and the outcomes of patients with HF in a Chinese population. Patients with HF and serum Se examination were retrospectively included. Baseline information were collected at patient’s first admission. The primary and secondary outcomes were all-cause mortality and rehospitalization for HF during follow-up, respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Since the discovery of Se involvement in Keshan’s Disease more than fifty years ago [ 2 , 23 , 93 ], the knowledge of the involvement of Se in cardiovascular diseases has expanded significantly. Se is now known to participate in a host of different cardiovascular disorders, including myocardial infarction, heart failure, cardiomyopathies, atherosclerosis, and coronary heart disease, as Se deficiency is associated with increased risk of these cardiovascular diseases [ 4 , 5 , 30 , 99 , 117 ]. Therefore, it is unsurprising that Se supplementation has been explored as a potential therapeutic to treat several of these cardiovascular disorders when they are linked to a deficient intake status for Se.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the discovery of Se involvement in Keshan’s Disease more than fifty years ago [ 2 , 23 , 93 ], the knowledge of the involvement of Se in cardiovascular diseases has expanded significantly. Se is now known to participate in a host of different cardiovascular disorders, including myocardial infarction, heart failure, cardiomyopathies, atherosclerosis, and coronary heart disease, as Se deficiency is associated with increased risk of these cardiovascular diseases [ 4 , 5 , 30 , 99 , 117 ]. Therefore, it is unsurprising that Se supplementation has been explored as a potential therapeutic to treat several of these cardiovascular disorders when they are linked to a deficient intake status for Se.…”
Section: Discussionmentioning
confidence: 99%
“…Se deficiency also is associated with heart failure [ 4 , 29 , 30 , 31 ]. Serum Se concentrations measured in a large European cohort of patients with worsening heart failure were low in 70% of these patients.…”
Section: The Relationship Between Se Deficiency and Cardiovascular Healthmentioning
confidence: 99%
“…Fifteen years ago, in our first Se study with CD patients [23] 96% of the participants showed Se levels < 100 mcg/L and 52% < 70 mcg/L. In a Chinese populational study including 411 patients with heart failure [53], the mean serum level of Se was of 68.3 ± 27.7 mcg/L. This study showed that lower serum Se level was significantly associated with increased risk of all-cause mortality in patients with heart failure, comparing patients in the highest quartile of Se levels (94.15-116.7 ng/mL), to those with lowest quartile (17.40-44.35…”
Section: Lessons From the First And Unique Se Trial In Chagas Diseasementioning
confidence: 94%
“…A direct correlation between serum Se levels and progression of heart disfunction, especially heart failure, is still under debate [14][15][16][17][52][53][54]. STCC also showed scattered basal levels of Se ranged from 40 to 150 ng/mL, a variability that deserves further studies for a clearest picture related to selenoprotein genetic polymorphisms and/or regional diets varying in Se content.…”
Section: Lessons From the First And Unique Se Trial In Chagas Diseasementioning
confidence: 98%
See 1 more Smart Citation